Review of Bicarinibracon Quicke & Walker and Chelonogastra Ashmead (Hymenoptera, Braconidae, Braconinae) in China, with the description of two new species - Yang Li; Cornelis van Achterberg; Cheng-Jin Yan; Xue-Xin Chen (Journal of Hymenoptera Research)
The species of two genera (Bicarinibracon Quicke & Walker and Chelonogastra Ashmead) of the subfamily Braconinae (Hymenoptera, Braconidae) from China are reviewed and 6 species are recognized, including 2 new species (Bicarinibracon concolor sp. nov. and Chelonogastra rugosa sp. nov.), which are described and illustrated. Bicarinibracon carini Chishti & Quicke, 1993 is reported from China for the first time. Keys to the Chinese species of the genera Bicarinibracon and Chelonogastra are provided.